2010
DOI: 10.1111/j.1863-2378.2010.01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Antibodies toEncephalitozoon cuniculiandToxoplasma gondiiin Farmed Domestic Rabbits in Egypt

Abstract: Rabbit sera from ten commercial farms representing three provinces in Northern Egypt (Behera, Alexandria and Khafr El-Sheikh) were submitted to serological screening for Encephalitozoon cuniculi using an enzyme-linked immunosorbent assay and for Toxoplasma gondii using an indirect hemagglutination test. Antibodies against E. cuniculi were detected in 36/240 (15%) sera examined while antibodies against T. gondii showed a seroprevalence of 22/194 (11.34%). Both infections were detected in all of the examined far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 31 publications
(54 reference statements)
3
16
1
Order By: Relevance
“…This seropositive rate of asymptomatic rabbits (25.8%) in the current study was higher than those reported in Nigeria (16.5%) but lower than in UK (36.8%), Japan (57.9%), and Italy (68.1%) [5,13]. Reports from different countries have shown different incidences suggesting that the prevalence may vary strongly in the same country from one locality to another due to certain ecological factors and breeding system [14]. In the current study, samples were collected from 3 areas including Daejeon city, Gyeongbuk, and Chungnam province in Korea, and the results of the seropositive rate showed different in each area.…”
contrasting
confidence: 52%
“…This seropositive rate of asymptomatic rabbits (25.8%) in the current study was higher than those reported in Nigeria (16.5%) but lower than in UK (36.8%), Japan (57.9%), and Italy (68.1%) [5,13]. Reports from different countries have shown different incidences suggesting that the prevalence may vary strongly in the same country from one locality to another due to certain ecological factors and breeding system [14]. In the current study, samples were collected from 3 areas including Daejeon city, Gyeongbuk, and Chungnam province in Korea, and the results of the seropositive rate showed different in each area.…”
contrasting
confidence: 52%
“…Antibodies to T. gondii were detected, e.g. by indirect haemagglutination test in 23.4 % (18/77) rabbits from China [8], by Enzyme-Linked Immuno Sorbent Assay (ELISA) in 15.5 % (103/1883) rabbits from the Czech Republic [9] and in 11 % (22/194) rabbits from Egypt [10], or by Modified Agglutination Test (MAT) in 16.3 % (70/429) rabbits from Mexico [11].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the organism has also been detected in other mammalian hosts, including rodents, horses, carnivores, non-human primates and humans [2,16]. Encephalitozoon cuniculi infections in rabbits show worldwide prevalence, and the seroprevalence has been reported to be 7.0% in breeding colonies in the U.S.A. [9], 59.2% in pet rabbits in England [10], 67.2% in pet rabbits in Italy [5] and 15% in farmed rabbits in Egypt [1]. In Japan, occasional cases of the infections have been reported since the 1990s [6,12,13,17], and a high seroprevalence of E. cuniculi has been recently reported in pet rabbits [11].…”
mentioning
confidence: 99%